Correlation and consistency between two detection methods for serum 25 hydroxyvitamin D levels in human venous blood and capillary blood - Xing, Yutong; Wang, Kaixi; Ma, Xinyu; Zhang, Huifeng; Tian, Xiaoyu (Frontiers in Nutrition, 2024)
The study assessed the correlation and concordance of 25-hydroxyvitamin D [25(OH)D] levels in capillary and venous plasma collected simultaneously after vitamin D3 supplementation in 42 healthy adults. They were randomly divided into three groups by random number table method. Group A took 1000 IU vitamin D3 daily, group B took 10000IU vitamin D3 every 10 days, and group C took 30000 IU vitamin D3 every 30 days until the end of the twelfth month. Venous blood serum 25(OH)D level was detected by chemiluminescence immunoassay (CLIA) and mass spectrometry (LC-MS) at day 1, day 14, day 28, month 6 and month 12 respectively, the capillary blood serum 25(OH)D level was detected by chemiluminescence immunoassay (CLIA) at the same time. Pearson correlation analysis and linear regression analysis were employed to investigate the relationship and transformation equation between the findings of the two samples and the results obtained from different detection methods within the same sample. The Bland-Altman method, Kappa analysis, and receiver operating characteristic (ROC) curve were utilized for assessing consistency, sensitivity, and specificity. Results: The three groups all reached a stable peak at 6 months, and the average levels of the three groups were 49.21, 42.50 and 43.025nmol/L, respectively. The average levels of group A were higher than those of group B and group C, (P<0.001).The mean values of serum 25(OH)D measured by LC-MS and CLIA in 42 healthy adults were 45.32 nmol/L and 49.88nmol/L, respectively, and the mean values of 25(OH)D measured by LC-MS in capillary blood were 52.03nmol/L， and the difference was statistically significant (P<0.001). Pearson correlation analysis showed that the linear fitting formula of scatter data was as follows: venous 25(OH)D concentration (nmol/L) = 1.105 * capillary 25(OH)D concentration -7.532 nmol/L, R2=0.625. Good agreement was observed between venous and corrected capillary 25 (OH) D levels in clinical diagnosis (Kappa value 0.75). The adjusted serum 25 (OH) D in capillary blood had a high clinical predictive value . Conclusions: The agreement between the two methods is good when the measured 25(OH)D level is higher. Standardized capillary blood chemiluminescence method can be used for 25(OH)D detection.